+0  
 
0
161
1
avatar+2308 

Simplify

 Nov 14, 2018

Best Answer 

 #1
avatar+7348 
+2

\(\ \phantom{=}\,\dfrac{\frac{u+4}{25}-\frac{u+4}{5}}{\frac{4}{u+4}}\\~\\ =\,(\frac{u+4}{25}-\frac{u+4}{5})\div\frac{4}{u+4}\\~\\ =\,(\frac{u+4}{25}-\frac{u+4}{5})\cdot\frac{u+4}{4}\\~\\ =\,(\frac{u+4}{25}-\frac{u+4}{5}\cdot\frac55)\cdot\frac{u+4}{4}\\~\\ =\,(\frac{u+4}{25}-\frac{5(u+4)}{25})\cdot\frac{u+4}{4}\\~\\ =\,(\frac{1(u+4)-5(u+4)}{25})\cdot\frac{u+4}{4}\\~\\ =\,(\frac{-4(u+4)}{25})\cdot\frac{u+4}{4}\\~\\ =\,\frac{-4(u+4)(u+4)}{4(25)}\\~\\ =\,\frac{-(u+4)(u+4)}{25}\\~\\ =\,\frac{-(u+4)^2}{25} \)

.
 Nov 14, 2018
 #1
avatar+7348 
+2
Best Answer

\(\ \phantom{=}\,\dfrac{\frac{u+4}{25}-\frac{u+4}{5}}{\frac{4}{u+4}}\\~\\ =\,(\frac{u+4}{25}-\frac{u+4}{5})\div\frac{4}{u+4}\\~\\ =\,(\frac{u+4}{25}-\frac{u+4}{5})\cdot\frac{u+4}{4}\\~\\ =\,(\frac{u+4}{25}-\frac{u+4}{5}\cdot\frac55)\cdot\frac{u+4}{4}\\~\\ =\,(\frac{u+4}{25}-\frac{5(u+4)}{25})\cdot\frac{u+4}{4}\\~\\ =\,(\frac{1(u+4)-5(u+4)}{25})\cdot\frac{u+4}{4}\\~\\ =\,(\frac{-4(u+4)}{25})\cdot\frac{u+4}{4}\\~\\ =\,\frac{-4(u+4)(u+4)}{4(25)}\\~\\ =\,\frac{-(u+4)(u+4)}{25}\\~\\ =\,\frac{-(u+4)^2}{25} \)

hectictar Nov 14, 2018

34 Online Users

avatar
avatar
avatar
avatar
avatar
avatar
avatar
avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.